2020
DOI: 10.1021/acsami.0c00262
|View full text |Cite
|
Sign up to set email alerts
|

NiMo–NiCu Inexpensive Composite with High Activity for Hydrogen Evolution Reaction

Abstract: In this work, the effect of copper addition on NiMo coating is evaluated in regard to the hydrogen evolution reaction (HER). NiMo and NiMo–NiCu composites are prepared by a simple coelectrodeposition process. The effect of Cu on deposit characters were tested by varying it in the range of 0.06–0.20 molar ratio. Copper addition promotes the growth of a new crystalline phase: NiCu. Also, the copper addition changed the composite surface. NiMo–NiCu0.12 shows a surface roughness 30 times higher than the NiMo mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 60 publications
4
32
1
Order By: Relevance
“…EIS measurements were also conducted to provide more information at the electrode−electrolyte interface (Figure 3c). Note that the first semicircle in the highfrequency region of the Nyquist plots was related to the electrode texture and was independent of the kinetics of the faradaic process, 33 These results confirm that the metal/metal oxide did not change.…”
Section: ■ Results and Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…EIS measurements were also conducted to provide more information at the electrode−electrolyte interface (Figure 3c). Note that the first semicircle in the highfrequency region of the Nyquist plots was related to the electrode texture and was independent of the kinetics of the faradaic process, 33 These results confirm that the metal/metal oxide did not change.…”
Section: ■ Results and Discussionsupporting
confidence: 59%
“…EIS measurements were also conducted to provide more information at the electrode–electrolyte interface (Figure c). Note that the first semicircle in the high-frequency region of the Nyquist plots was related to the electrode texture and was independent of the kinetics of the faradaic process, while the second semicircle in the low-frequency region refers to the charge transfer resistance ( R ct ) in the HER. As expected, the Ni–Mo–O/Ni 4 Mo@NC exhibits a smaller R ct than that of Ni–Mo–O, suggesting the fast electron transport on the Ni–Mo–O/Ni 4 Mo@NC interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The EIS measurements for all the samples were performed with a frequency range from 0.1 Hz to 100 kHz, and the resulting Nyquist plots comprising of semicircles are presented in Figure 8. The starting point of the semicircle signifies the internal resistance (also known as solution resistance (R S )) of the catalyst, whereas the diameter of the semicircle denotes chargetransfer resistance between the electrode-electrolyte interfaces (R CT ) [26]. In terms of equivalent circuit, the depressed semicircle is represented by R S connected in series to the capacitor (Q DL ) and R CT in a parallel arrangement, as shown in Figure 8.…”
Section: 𝑂𝐻 → 𝑂𝐻 * + 𝑒mentioning
confidence: 99%
“…NiÀ W, NiÀ MoÀ Fe, and NiÀ MoÀ Co [78] are few examples of Ni-based alloys that have been broadly studied for HER and they can also be applied as cocatalyst in photocathodes. Recently, Santos et al [79,80] have shown that a copper insertion in NiÀ Mo and CoÀ Mo alloys can increase catalytic activity and reduce overpotential. The addition of Cu in NiÀ Mo decreased the overpotential in almost half of the values obtained for NiÀ Mo electrodes (η = À 154 mV dec À 1 for NiÀ Mo and η = À 86 mV dec À 1 for NiÀ MoÀ Cu at À 10 mA cm À 2 ).…”
Section: Summary and Perspectivesmentioning
confidence: 99%